2022
DOI: 10.1155/2022/8152971
|View full text |Cite|
|
Sign up to set email alerts
|

An Empirical Analysis of Mental Health and Social Support in the Elderly of Different Age Groups: A Survey and Analysis of Data from China

Abstract: To explore the effects of social support on the mental health of older adults in different age groups in China, and to provide reference for the development of social support policies to promote the mental health of older adults in China. This paper uses a random sampling method to conduct a questionnaire survey of 3,000 older adults aged 60 years or older in Nanjing and a dichotomous logistic regression model for empirical analysis. The two dimensions of mental health and social adjustment were used to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Age (or generation) has been one of the demographic variables that has received substantial interest in mental health research 38 , 39 . Some studies focused on a specific age group for analysis, while others compared different age groups 40 43 . Many studies have paid attention to different age groups influenced by the COVID-19 pandemic 44 46 .…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Age (or generation) has been one of the demographic variables that has received substantial interest in mental health research 38 , 39 . Some studies focused on a specific age group for analysis, while others compared different age groups 40 43 . Many studies have paid attention to different age groups influenced by the COVID-19 pandemic 44 46 .…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Social support may have different effects on older adults' health due to the different age groups they are in (Litwin and Stoeckel, 2013;Qiang and Liu, 2022). A study has shown that objective and subjective support have significant positive effects on the mental health of older adults aged 70-79 years and ≥ 80 years, while support utilization has greater effects on the health of older adults aged 60-69 years (Qiang and Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Social support may have different effects on older adults' health due to the different age groups they are in (Litwin and Stoeckel, 2013;Qiang and Liu, 2022). A study has shown that objective and subjective support have significant positive effects on the mental health of older adults aged 70-79 years and ≥ 80 years, while support utilization has greater effects on the health of older adults aged 60-69 years (Qiang and Liu, 2022). In respect of older adults over the age of 80 years, it has been found that living with a spouse actually reduced their quality of life, but the opposite was true for those aged 60-79 years who experienced an improvement in their quality of life (Litwin and Stoeckel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%